Voices that Matter: The Attic Echoes Through the House - Monteiro, Flávia Rodrigues (Revista Estudos Feministas, 2018)
In The Buddha in the Attic, Julie Otsuka explores two main topics: the Picture Bride practice and the internment camps for Japanese Americans during World War II. An analysis of the development of both topics in the narrative reveals parallels with potential issues faced by women and diasporic subjects in contemporaneity, connecting with theoretical approaches on these topics. It is interesting to note that the narrative is mainly developed in first person plural with occasional expansion to other subjects such as “I”, “she”, “he”, and even “you”. The effect of this game between singular and plural is a narrative that describes a collective experience but avoids essentialisms. Even though it focuses on Women’s voices, the novel also explores different subjectivities involved in the diasporic experience. Thus, Otsuka’s narrative gives voice to disempowered subjects long locked in the attic of history and makes their voices echo through the houses of contemporaneity